Emergency contraception: knowledge, attitude and awareness of its usage among medical students in a private medical college of Davangere - Chandramohan, Malavika Jabin; Prabhudev, Prema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Emergency contraception (EC) is the contraception used to prevent pregnancy after unintended or unprotected sexual intercourse. EC can be used after contraceptive failure or misuse (as in slippage or breakage of condoms, forgotten pills). It is used before the time of implantation and prevents pregnancy in 75-99% of the cases. EC is available as pills or IUCD. Methods: A cross-sectional study involving final year medical students was conducted at SSIMS and RC, Davangere, Karnataka, India. A 32-point questionnaire encompassing the socio-demographic details, knowledge and attitude towards EC was answered by a total 146 participants. The data were entered in Microsoft excel sheet and the descriptive statistics were analysed using Epi-info software Results: Majority of the participants had heard about EC and also knew the trade name under which it is available. The main indication for EC usage was thought to be unprotected sex by 76% participants. Nearly 90% participants knew that EC does not protect against STDs. 85% participants thought that failures can happen despite EC usage. On assessing the attitude, majority disagreed to the notion that EC usage promotes promiscuity and using EC is a sinful act. Conclusions: Knowledge and attitude regarding EC and its usage was fairly good among the medical students in our study. The inclusion of EC in medical curriculum has added to their knowledge. Being the responsible future physicians, their knowledge with regard to EC is deemed important. Similarly, an awareness regarding EC should be spread across the general public to prevent the unwanted pregnancies and its consequences.